ANALISIS HUKUM ISLAM DAN HUKUM ADAT TERHADAP TRADISI PERKAWINAN MASYARAKAT BERDASARKAN PRIMBON (STUDI KASUS DI DESA KUMBANG SARI KEC. JANGKAR KAB. SITUBONDO) - Haris, Haris Mahfud Khoirul Anam; Ismail Marzuki (IAI Darussalam, 2023)
Culture is the legacy of our ancestors. Some people believe culture is something that is sacred and important to do because it has a good impact and some people also believe that custom or culture can cause bad things if it is not practiced in life. Javanese society is still thick with all its culture, one example of marriage culture. Marriage is a very sacred procession in which there are many things that must be passed, especially for Javanese people. Before carrying out marriages, Javanese people usually carry out auspicious day calculations which are often called primbon. Where this primbon is done to calculate the pros and cons of a family of couples who will marry. In this study, the researcher focused on the analysis of Islamic law and customary law on community marriage traditions based on primbon (a case study in the village Kumbang Sari, Jangkar District, Situbondo Regency). the author finds that the local community still adheres to adat, especially in matters of marriage. On this occasion, the author will reveal about the process of calculating good days and good dates (Primbon) according to the views of customary law and Islamic law. The author thinks this research is very good, considering that in this era there are not many people who preserve customs and culture, field studies in the village of Kambang sari the authors found that the majority of the people there still adhere to Javanese customs, especially regarding marriage in terms of determining auspicious days and auspicious dates. in a marriage.